Aerobiologia - Aerobiologia (Springer Nature, 2026)
Aerobiologia focuses on respiratory allergology, plant pathology, pest management, biological weathering and biodeterioration, indoor air quality, air-conditioning technology and industrial aerobiology. The journal offers interdisciplinary coverage of aerobiology and interaction of human, plant and animal systems on the biosphere. It serves aerobiologists, and other professionals in medicine, public health, industrial and environmental hygiene, biological sciences, agriculture, atmospheric physics, botany, environmental science and cultural heritage.
FI 0.44
Q2
Keywords: Earth; Space & Environmental Sciences; Atmospheric Sciences; Ciencias atmosféricas; Acuerdos transformativos; Transformative agreements; Medicina; Salud pública; Higiene industrial y ambiental; Ciencias biológicas; Agricultura; Física atmosférica; Botánica; Ciencias ambientales; Patrimonio cultural